PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus pada Bagian Produksi 1 PT JS Jakarta) - Trisnawaty, Martina; Parwoto, Parwoto (Universitas Muhammadiyah Surakarta, 2020)
ABSTRACTPT JS Jakarta is a company enganged in the manufacturing of handbag and wallet industries experiencing problems, where employee work productivity, especially the production part is still low, where it is allegedly less conducive of work environment and workloads that are overload, which is not according to employee expectations. The purpose of this study is to analyze the effect of work environment and workload on employee work productivity at PT JS Jakarta Department Production 1. The population in this study all employees of the department production 1 of PT. JS Jakarta, amounting to 530 people. The sample used is 84 people, calculated based on solvin formula. The sampling method uses probability sampling with the research Proportionate Stratified Random Sampling. The method of data collections using observation and questionnaire. The data analysis method using IBM SPSS version 22. This study proves that (1) work environment have a positive and significant effect on employee work productivity, (2) workloaf have a negatif and significant effect on employee work productivity.Â